Retirement Literacy Among Gen Z in Malaysia : A Baseline Study on Financial Knowledge, Savings Behavior, and Investment Preferences. - Hana, Hamidi; Victoria, Jonathan; Helmi, Sumilan (Employees Provident Fund (EPF), 2025)
This baseline study examines the retirement literacy of Gen Z in Malaysia, focusing on their financial knowledge, saving behaviors, and investment preferences. A survey was conducted among 76 respondents, revealing that while many are aware of retirement planning concepts, a significant portion lacks formal financial education. The findings indicate that 42.1% of respondents save inconsistently, while 35.5% do not currently save but plan to start soon. Financial constraints and short-term priorities were cited as primary barriers, with 71.1% highlighting insufficient funds as a key reason. Most respondents believe that government retirement funds will not be sufficient, and concerns over inflation and healthcare costs were prominent. Investment preferences favored safer options like EPF contributions (92.1%) and fixed deposits (32.9%). The study suggests that mandatory financial education in schools and universities could enhance retirement literacy. As a foundational investigation, this study provides insights for policymakers and financial educators to develop targeted interventions that improve Gen Z's long-term financial security (Lusardi & Mitchell, 2011a; OECD, 2020).